The Relationship of Intellectual Capital to Institutional Excellence: Applied Study on the Medical Tourism Administration, Ministry of Tourism - Alwakeel, Eman (The Arab Journal of Administration, 2021)
The study aimed to examine the relationship between intellectual capital and institutional excellence in the Ministry of Tourism, Department of Therapeutic Tourism, and explore the relationship of intellectual capital in terms of organizational capital component and innovation and creativity component of institutional excellence. Medical tourism in the Egyptian Ministry of Tourism? The researcher developed three hypotheses: There is no statistically significant relationship between the intellectual capital in terms of human capital component and institutional excellence in the Department of Medical Tourism in the Egyptian Ministry of Tourism, There is no statistically significant relationship between intellectual capital in terms of organizational capital component and institutional excellence in the Department of Medical Tourism in the Egyptian Ministry of Tourism, There is no statistically significant relationship between the intellectual capital in terms of the component of innovation, creativity and institutional excellence in the management of medical tourism in the Egyptian Ministry of Tourism. The results show that there is a correlation and influence on the part of the intellectual capital in terms of the organizational and innovative component. The study also revealed that the reality of capital with its components related to the organizational and innovative elements contributes to the completion of the institutional system that provides appropriate dimensions and environment to achieve excellence in the management of medical tourism. The statistical relations of the three research hypotheses and the impact of organizational capital, human capital and intellectual capital on the distinguished institutional performance in the management of medical tourism were demonstrated. The study recommended drawing up a plan for human resources and practicing it from the basis of organizational and innovative intellectual capital, The Medical Tourism Administration in the Ministry of Tourism should implement a system of material and moral recognition for individuals who contribute their performance to ideas that add tangible value to activities and enhance the return on medical tourism management, Develop the organizational structure of the management of medical tourism in accordance with the standards of intellectual capital in terms of providing an environment for innovation and creativity.